Method of preparation individual instrument for knee arthroplasty - Golovakha, Maxim; Bondarenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective. To improve the results of total knee arthroplasty by developing a methodology for the design and manufacture of an individual instrument for the implants accuracy installation. Methods. An analysis of the literature on various concepts of alignment was carried out. In practice, one of them was chosen depending on the clinical case. For preoperative planning, a CT scan of the lower extremities was performed with the capture of the pelvis or hip joint; feet completely or up to the calcaneus (CT 64 or 128 slices were used for better visualization and increased accuracy). With the help of RadiAnt DICOM, the 3D model was converted into an STL file, which was uploaded to the FreeformPlus program, where preoperative planning was done. The program allows not only to assess the presence of varus or valgus deformity of the limb, to determine its degree, but also other deformities of the lower legs. In the program, after assessing the deformity, we perform preoperative planning using one of the concepts: anatomical, mechanical, or kinematic. After choosing the concept and virtual correction of the limb, we prepare an individual instrument and print is with additive technology. In addition, we print joint parts of the femur and tibia, which allows the surgeon to orient himself intraoperatively. Results. Thanks to the completed work and software, it was possible to improve the results of knee arthroplasty by increasing accuracy implants installing. The developed technique of 3D-design and manufacture of an individual tool allowed us to use any of the alignment concepts with high accuracy. Preoperative planning increases the deformity understanding because surgeon himself, not the engineer, does it. Conclusions. Developed technique of three-dimensional modeling of the lower extremity makes it possible to correctly plan, manufacture and put into practice a patient specific tool for knee arthroplasty, taking into account the individual characteristics of the lower extremity.